2023
DOI: 10.1007/jhep01(2023)120
|View full text |Cite
|
Sign up to set email alerts
|

Spread complexity and topological transitions in the Kitaev chain

Abstract: A number of recent works have argued that quantum complexity, a well-known concept in computer science that has re-emerged recently in the context of the physics of black holes, may be used as an efficient probe of novel phenomena such as quantum chaos and even quantum phase transitions. In this article, we provide further support for the latter, using a 1-dimensional p-wave superconductor — the Kitaev chain — as a prototype of a system displaying a topological phase transition. The Hamiltonian of the Kitaev c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 69 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Consequently, in some sense, the SC can be thought to provide a robust characterization of QPTs using information theoretic quantities. Furthermore, in [59,60], the SC was used to study topological phase transition in SSH and Kitaev models, respectively, in both in-and out-of-equilibrium scenarios, and the utility of SC as a marker of phase transition was established. In our work, though, we have mainly focused on the zero-temperature QPTs in an infinite range interacting LMG model, we briefly consider quenches in the SSH model showing the topological phase transition in the appendix below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, in some sense, the SC can be thought to provide a robust characterization of QPTs using information theoretic quantities. Furthermore, in [59,60], the SC was used to study topological phase transition in SSH and Kitaev models, respectively, in both in-and out-of-equilibrium scenarios, and the utility of SC as a marker of phase transition was established. In our work, though, we have mainly focused on the zero-temperature QPTs in an infinite range interacting LMG model, we briefly consider quenches in the SSH model showing the topological phase transition in the appendix below.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the complete set of Lanczos coefficients can be obtained from the 'survival amplitude', which is the overlap between the initial reference state and the unitary evolved target state. This notion of SC was explored further in [59] to distinguish different topological phases of the Su-Schrieffer-Heeger (SSH) model and in the Kitaev chain [60]. It was concluded that the SC shows markedly different behavior in the two phases, in contrast to that of the NC.…”
Section: J Stat Mech (2023) 103101mentioning
confidence: 99%
“…This orthonormal basis is known as the Krylov basis, and in a sense is an optimal choice of basis in Krylov space. In the context of quantum state complexity, the Krylov basis has been shown to minimize the spread complexity [29,33,77].…”
Section: Jhep05(2023)226mentioning
confidence: 99%
“…Often called as 'spread complexity,' in its simplest avatar it is associated to the optimal spread of a particular state under timeevolution [31]. Recently, this has found applications in the context of quantum many-body theory [31][32][33][34][35][36][37][38][39]. The notion of quantum complexity comes from the theory of quantum computation.…”
Section: Introductionmentioning
confidence: 99%